Tanggungjawab Pemilik Hewan Peliharaan Bagi Korban Gigitan Anjing Rabies Di Tinjau Dari Kuhperdata Di Kabupaten Belu - Febrini Welhelmina Asa; Darius Mauritsius; Helsina F Pello (Artemis Law Journal, 2026)
The implementation of the legal responsibility of animal owners towards victims of rabies dog bites in Belu Regency is de jure regulated by Articles 1365 and 1368 of the Civil Code. However, de facto, this system experiences systemic dysfunction due to various structural and socio-cultural obstacles: (1) Internal factors of animal owners—as seen from the low level of education among owners (50% only have elementary/junior high school education) related to a lack of knowledge about the law (66.7% do not understand legal obligations), an indifferent attitude (“bites are not considered a serious problem”), and negligence in supervision (dogs are allowed to roam without vaccination); (2) External factors—consisting of difficulties in proving animal ownership (lack of dog identification), minimal access for victims to reach legal mechanisms (66.7% of victims do not know the reporting procedure), and weak supervision from the government (incomplete socialization, lack of firm sanctions); (3) Systemic impact—only 33.3% of victims received accountability (customary treatment/mediation costs), but 50% of animal owners refused to accept responsibility, leaving victims trapped in a justice vacuum that worsens the potential for a rabies outbreak. Sustainable solutions are needed through multidimensional interventions: application of administrative sanctions, legal education based on culture, and cooperation between agencies (Livestock Service, Health Service, and Police). Without this synergy, victims will remain the most disadvantaged party in a legal system that is not yet functioning optimally.